Characteristics of pores in coals exposed to acid mine drainage. (November 2021) - Tang, Hao; Luo, Jin-zhi; Zheng, Li-wei; Liu, Chi-yang; Li, Hua-hua; Wu, Guan-nan; Zeng, Meng-li; Bai, Xue-song
Abstract: Acid mine drainage commonly occupies some pore space after underground coal mining, and this severely depreciates coal pillars, thereby posing a significant risk to mine stability. Considering that such depreciation is reflected in the microstructures of these pillars, in the present study, we propose a static immersion method suitable for coal seam samples immersion in the laboratory. We immersed the No. 2–2 coal seam samples from the Ningtiao Tower Coal Mine in Yulin, Shaanxi Province, in different acid mine drainage solutions and monitored the pH, oxidation–reduction potential (ORP), electrical conductivity (EC), total dissolved solids (TDS) among other water quality parameters for 300 h. After the immersion tests, samples were examined using scanning electron microscopy (SEM). The pH, ORP, EC, and TDS of the prepared acid mine drainage solutions increased significantly as the immersion time increased. Changes in water quality parameters are attributed to the absorption of hydrogen ions by insoluble clay minerals in the coal, which reduced the acidity, increased the pH value, and enhanced the electrical conductivity of the acid mine drainage solutions. SEM analysis reveals differences in the pore characteristics of (pore throat size and orientation) of the coal samples, and these are caused by erosive effects of the acid mine drainage solutions. Pores with throat sizes greater than 10 μ m increased by 95% as the pH of the acid mine drainage solutions decreased, while the dominant pore orientation (60–90°) decreased to the 0–30° or increased to the 150–180° range, thereby increasing their randomness.